Short- and Long-Term Outcomes of Totally Versus Hybrid Minimally Invasive Ivor Lewis Oesophagectomy for Oesophageal Cancer: A Propensity Score-Matched Analysis - Gu, Yi-Min; Zhang, Han-Lu; Yang, Yu-Shang; Yuan, Yong; Hu, Yang; Che, Guo-Wei; Chen, Long-Qi; Wang, Wen-Ping (Frontiers in Oncology, 2022)
Background: Few objective studies have compared totally minimally invasive Ivor Lewis oesophagectomy with hybrid procedure. Here we investigated whether the choice between totally and hybrid minimally invasive Ivor Lewis oesophagectomy influenced short-term outcomes and long-term patient survival. Methods: Patients who underwent totally or hybrid minimally invasive Ivor Lewis oesophagectomy between January 2014 and December 2017 were propensity score matched in a 1:1 ratio. The short- and long-term outcomes between the two groups were compared before and after matching. Results: Of 138 totally and 156 hybrid minimally invasive oesophagectomy patients were eligible, 104 patients from each group were propensity score matched. Totally minimally invasive oesophagectomy was associated significantly with less blood loss (median(IQR) 100(60–150) vs 120(120–200) ml respectively; P < 0.001), pneumonia (13.5 vs 25.0%; P = 0.035), pleural effusion (3.8 vs 13.5%; P = 0.014), and chest drainage (7.5(6–9) vs 8(7–9) days; P = 0.009) than hybrid procedure. There was no significant difference in 3-year overall survival rate and 3-year disease-free survival rate between the two group. Conclusions: Totally minimally invasive Ivor Lewis oesophagectomy may improve short-term outcomes and specifically reduce the incidence of pulmonary complications compared with hybrid procedure. The long-term overall survival and disease-free survival rates between the two groups were similar.